Pendampingan Pengelolaan Aset Desa, Serta Inovasi Iptek Membangun Keunggulan Kompetitif Berbasis Aset Desa Di Desa Mandalamekar, Kecamatan Cimenyan, Kabupaten Bandung, Jawa Barat - Subing, Hesty Juni Tambuati; Hidayati, Rini; Asaari, Masagus; Shaleh, Khairul (Jurnal Mandala Pengabdian Masyarakat, 2024)
The mismatch between the competencies and roles of village officials often hampers the process of reporting and managing village assets effectively. Therefore, one of the focuses of the community service program conducted in Mandalamekar village government, Bandung Regency, West Java Province is to enhance the skills of village officials in manage and documenting village assets. The village officials will receive specialized guidance on village asset administration and management.The program will be run through a training method that aims to refine and improve participants' skills. This activity will provide lessons on basic concepts as well as practical techniques in asset management and administration. Furthermore, village officials are expected to conduct simulations in preparing accountability reports. To ensure optimal results, we will include continuous assistance to village officials through the use of SIPADES. This application is designed to facilitate village officials in managing and reporting assets efficiently and in accordance with applicable regulations.SIPADES, which is a web-based application, will help village officials improve their capabilities in information and communication technology, while building a competitive advantage. Through this service, several outputs are expected, including an increase in human resource competencies in Mandalamekar Village, the preparation of one scientific article with ISSN, publication of articles in electronic media, and the making of videos that will be aired on Yarsi TV. The results of this PKM show that village officials are able and skilled in preparing financial reports and managing village assets properly.